Studi Literatur: Optimalisasi Pembelajaran Pemrograman dengan Sistem Berbasis AI - Rizky Nur Azizah; Binastya Anggara Sekti (Ikatan Ahli Informatika Indonesia, 2024)
Artificial intelligence (AI) has opened up new opportunities in various fields, including education. AI makes it possible to optimize the teaching-learning process in the context of programming learning, which is often considered challenging by many students. This research aims to explore the potential for optimizing programming learning through the implementation of an AI-based online learning system. The method used is a literature study, which involves researching various sources that discuss the use of AI in education, particularly in the context of programming learning. The literature approach includes analyzing and synthesizing data from journals, books, and conference articles that discuss AI techniques such as machine learning, recommendation systems, and real-time feedback. The results show that using AI in online learning platforms can increase student engagement, accelerate feedback, and improve personalization of learning materials. However, there are some challenges when implementing these systems, such as the need for adequate technological infrastructure and teacher training. In conclusion, although AI has a lot of potential to optimize programming learning, effective implementation requires technical and pedagogical considerations. According to this study, further research is needed to overcome implementation barriers and assess the long-term effects of using AI in programming education.